Understanding leader-follower dynamics in organization: An overview / Azlyn Ahmad Zawawi - Ahmad Zawawi, Azlyn (2010)
Leader and follower connect themselves through synergic dynamics. More often than not, they identify themselves as a unit and practically plan organizational development and progress to achieve similar strategies and objectives. Graen and Uhl-Bien (1995) stated that the development of a leader-member exchange is based on characteristics of the ‘working relationship’ as opposed to a personal or friendship relationship. Leaders create unity through demonstration of group-mindedness by making more references to the collective history, the collective identity and interests, and collective efficacy (Shamir, House & Arthur, 1993). The more leaders augment follower identification (through role modeling or group socialization), the more followers will likely experience higher feelings of ownership and responsibility (Dick et.al, 2007). To understand these dynamics, reciprocal effect of both parties are reviewed and discussed. This paper intends to recognize the relationship of leader and follower and how they relate to each other in groups.